2018
DOI: 10.1016/j.mex.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Soil heterotrophic respiration assessment using minimally disturbed soil microcosm cores

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Gaseous N 2 O-N and CO 2 -C fluxes were calculated on soil mass basis by considering the linear increase in headspace concentration over the incubation period according to [71]. The ideal gas law was used to convert ppm of N 2 O and CO 2 in ppm, to N and C mass.…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Gaseous N 2 O-N and CO 2 -C fluxes were calculated on soil mass basis by considering the linear increase in headspace concentration over the incubation period according to [71]. The ideal gas law was used to convert ppm of N 2 O and CO 2 in ppm, to N and C mass.…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
“…Cf = (P*Mwc*1000)/(R*T) (5) where Cf is the conversion factor (ppm to µg m 3 ); P is the air pressure (in kPa); Mwc is the molar mass of N or C; R is the gas constant (8.314); T is the incubation air temperature (K) [71].…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
“…Baseline biochemical and physicochemical properties were then determined. The remainder of each composite sample was stored in separate containers and left to settle in the dark for 1 week at 15 • C (Zeng, 2017;Comeau et al, 2018;Randle-Boggis et al, 2018).…”
Section: Soil Samplingmentioning
confidence: 99%
“…If possible, undisturbed soil cores are sampled with stainless steel volumetric rings (bulk density rings), following the method proposed by Comeau et al. [9] . Many deep Bh, however, are too hard for a non-disturbing sampling.…”
Section: Field Samplingmentioning
confidence: 99%
“…Drying the samples or bringing them to field capacity will therefore be a radical ecological change for the existing microbial communities, which could alter the respiration rates. Recent studies have shown that ex-situ measurement of soil respiration with pre-dried and disturbed samples can give questionable results [9] .…”
Section: Introductionmentioning
confidence: 99%